Prevalence and management of chelonian shell fractures in a veterinary teaching hospital in Klang Valley, Malaysia (2022-2024) - Tasneem Rafiee (2025)
An abstract of the research paper is presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 –Research Project. Shell fracture is one of the most common traumatic injuries that affect chelonians, often requiring veterinary intervention. Despite regular presentation of chelonian cases to the University Veterinary Hospital, Universiti Putra Malaysia (UVH UPM), the prevalence and clinical management of shell fracture cases have not been previously characterised. This retrospective cohort study reviewed chelonian medical records from 2022 to 2024 (n = 123) to determine the prevalence of shell fracture cases and describe their clinical management. Four cases met the inclusion criteria, resulting in a prevalence of 3.25%. Three cases involved tortoises and one involved a terrapin, all of which were captively reared. Vehicular trauma accounted for 50% of the fractures, while one case resulted from a fall and the cause of one case was unrecorded. Diagnostic evaluation consisted primarily of physical examination and radiography, with imaging performed in 75% of cases to assess concurrent injuries. Shell fracture types include open, nondisplaced (n = 3) and closed (n = 1) fracture, while other clinical conditions associated with the fracture include dull mentation, hindlimb weakness, and evidence of systemic bleeding in one patient. Management approaches included wound cleaning, fluid therapy, analgesia and antibiotic administration, and fracture repair using epoxy glue. Two patients returned for follow-up, while outcomes for the remaining two were not documented.